Exploring the Transitions Associated with Aging in Two Northern First Nations Communities - St-Jean, Mélanie (Université d'Ottawa / University of Ottawa, 2013)
First Nations people have experienced dramatic life changes in a very short period of time. The process of change was not a conscious decision made by First Nations peoples but rather the result of successive stages of European contact and formal colonization by what is now the government of Canada. With such constant changes and the history of assimilation that overshadows the Aboriginal population, it is becoming difficult for Elders to sustain their roles within the family unit and in their community as a whole. This study provides a description of the oral accounts of Elders living in two remote First Nations communities in Northwestern Ontario. I conducted three summers of ethnographic research that involved participant observation of local cultural practices and 12 semi-structured interviews from 2009 to 2011. Guided discussions with Elders about their lives and their relationship to the land provide important insight into local cultural and personal values. Three primary themes emerged from the conversations with the Elders about life during the childhood: the intense physicality of life in the past, the connection between health and local foods and the changing role of Elders. Findings suggest that Elders are eager to transmit their knowledge to provide a healthier lifestyle for future generations. In addition, I provide a description of the current living conditions of Elders in both communities. First Nations Elders, who were once crucial to the survival of a band, are now facing the highest degree of vulnerability and are desperately searching for a new identity that gives them purpose. Meeting with Elders in their homes and at several community events provided insight into their lives and the challenges they are currently facing. These challenges and experiences are hardly one-dimensional, as they each have varying degrees of family support, financial stability and housing conditions. However, the consistent thread in all the cases was the ongoing struggle Elders have faced trying to reconcile traditional perspectives with the growing dominance of contemporary western lifestyle practices.
Keywords: First Nations; Knowledge; Elders; Changes; Aging; Transitions; Aboriginal; Northern Ontario; Care; Health